Do mothers sound good? A systematic review of the effects of maternal voice exposure on preterm infants' development. (May 2018) - Provenzi, Livio; Broso, Sara; Montirosso, Rosario
Highlights: Preterm infants are precociously separated from the mother. Maternal voice might facilitate mother-infant contact during hospitalization. A systematic review of maternal voice effects was carried on. Robust effects emerged for feeding, cognitive and neurobehavioral development. Maternal voice exposure should be delivered to preterm infants and their mothers. Abstract: Preterm infants are hospitalized in the Neonatal Intensive Care Unit (NICU) and are precociously separated from their mothers. Although developmental care interventions are meant to facilitate mother-infant bonding, physical contact is not always possible. Maternal voice exposure has been proposed as a way to foster maternal closeness and support postnatal bonding. Here we present a systematic review on maternal voice effects on preterm infants' development. Literature search occurred on 4 databases (PubMed, Scopus, Web of Science and CINAHL). Preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines have been adopted and standardized quality appraisal has been carried on. Wide differences emerged in infants' characteristics and maternal voice exposure methods. Inconsistency emerged for physiological outcomes (e.g., heart rate variability, oxygen saturation, number of critical alarm events), whereas a robust pattern of findings emerged for feeding behaviors, as well as cognitive and neurobehavioral development. Maternal voice appears to be a non-noxious intervention, which is consistent with developmental care and which can be embedded in developmental care strategies.